Age-Related Sexual Dimorphism in Temporal Discrimination and in Adult-Onset Dystonia Suggests GABAergic Mechanisms. - Reilly, Richard; Walsh, Richard; Walsh, Cathal (My University, 2015)
BACKGROUND: Adult-onset isolated focal dystonia (AOIFD) presenting in early adult life is more frequent in men, whereas in middle age it is female predominant. Temporal discrimination, an endophenotype of adult-onset idiopathic isolated focal dystonia, shows evidence of sexual dimorphism in healthy participants. OBJECTIVES: We assessed the distinctive features of age-related sexual dimorphism of (i) sex ratios in dystonia phenotypes and (ii) sexual dimorphism in temporal discrimination in unaffected relatives of cervical dystonia patients. METHODS: We performed (i) a meta-regression analysis of the proportion of men in published cohorts of phenotypes of adult-onset dystonia in relation to their mean age of onset and (ii) an analysis of temporal discrimination thresholds in 220 unaffected first-degree relatives (125 women) of cervical dystonia patients. RESULTS: In 53 studies of dystonia phenotypes, the proportion of men showed a highly significant negative association with mean age of onset (p < 0.0001, pseudo-R (2) = 59.6%), with increasing female predominance from 40 years of age. Age of onset and phenotype together explained 92.8% of the variance in proportion of men. Temporal discrimination in relatives under the age of 35 years is faster in women than men but the age-related rate of deterioration in women is twice that of men; after 45 years of age, men have faster temporal discrimination than women. CONCLUSION: Temporal discrimination in unaffected relatives of cervical dystonia patients and sex ratios in adult-onset dystonia phenotypes show similar patterns of age-related sexual dimorphism. Such age-related sexual dimorphism in temporal discrimination and adult-onset focal dystonia may reflect common underlying mechanisms. Cerebral GABA levels have been reported to show similar age-related sexual dimorphism in healthy participants and may be the mechanism underlying the observed age-related sexual dimorphism in temporal discrimination and the sex ratios in AOIFD.
PUBLISHED
Keywords: adult-onset isolated focal dystonia; penetrance; sex ratio; sexual dimorphism; temporal discrimination; Neuroscience